2020
DOI: 10.1109/access.2020.3009298
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of the Internet of Things in Agriculture: A Survey

Abstract: A rise in the population has immensely increased the pressure on the agriculture sector. With the advent of technology, this decade is witnessing a shift from conventional approaches to the most advanced ones. The Internet of Things (IoT) has transformed both the quality and quantity of the agriculture sector. Hybridization of species along with the real-time monitoring of the farms paved a way for resource optimization. Scientists, research institutions, academicians, and most nations across the globe are mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(70 citation statements)
references
References 163 publications
1
66
0
3
Order By: Relevance
“…Producers need backing to effectively actualize new advancements to guarantee achievement. At Decisive Farming, we uphold our cultivators with preparing and mastery [12]. 4.…”
Section: Gps Soil Examiningmentioning
confidence: 99%
“…Producers need backing to effectively actualize new advancements to guarantee achievement. At Decisive Farming, we uphold our cultivators with preparing and mastery [12]. 4.…”
Section: Gps Soil Examiningmentioning
confidence: 99%
“…Smallholder agriculture sustains close to 60 % of the global rural population ( Zavatta, 2014 ) and 70 % of the rural population in sub-Saharan Africa (SSA) as a primary source of livelihood ( Davis et al, 2017 ). It contributes about 50 % of the national GDP in SSA ( Kour and Arora, 2020 ) and is posited to be the direct driver for a number of Sustainable Development Goals (SDGs) in the continent ( Sachs et al, 2019 ). Improving the productivity of these systems has been a central agenda for governments, donors and research organizations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the prime motivations towards this research trend is the increasing awareness of Internet-of-Things (IoT), where sensors are integral. IoT is one dominant research topic for improving agricultural yields (Kour and Arora [69]). It has contributed towards opening avenues for smart farming and PA, although there is some dominant research gap (Kour and Arora [69]).…”
Section: Wsn In Precision Agriculturementioning
confidence: 99%
“…IoT is one dominant research topic for improving agricultural yields (Kour and Arora [69]). It has contributed towards opening avenues for smart farming and PA, although there is some dominant research gap (Kour and Arora [69]). In this aspect, various forms of sensors have also been investigated towards PA, where it is found that support vector machine and random forest are dominant classification approaches (Kamath et al [70]).…”
Section: Wsn In Precision Agriculturementioning
confidence: 99%